1,3-Bis[5-(2-pyridyl)-1H-tetrazol-1-yl]propane - Li, Gao-Nan (International Union of Crystallography, 2008)
The title compound, C(15)H(14)N(10), is a multidentate ligand obtained by the reaction of 5-(2-pyridyl)tetrazole with 1,3-dibromopropane. The molecule consists of two 5-(2-pyridyl)-1H-tetrazol-1-yl units connected by a propylene bridge in a U-like conformation. A twofold rotation axis passes through the central C atom.